2013
DOI: 10.1128/aem.03263-12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of theIn SituGrowth Rates of Subsurface Geobacter Species

Abstract: dMolecular tools that can provide an estimate of the in situ growth rate of Geobacter species could improve understanding of dissimilatory metal reduction in a diversity of environments. Whole-genome microarray analyses of a subsurface isolate of Geobacter uraniireducens, grown under a variety of conditions, identified a number of genes that are differentially expressed at different specific growth rates. Expression of two genes encoding ribosomal proteins, rpsC and rplL, was further evaluated with quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 65 publications
5
17
0
Order By: Relevance
“…Because of the lack of organic substrate, it was difficult for the electrogenic microorganisms to compete efficiently, in particular taking into account the origin of the seeded sludge. This observation has been previously reported in the literature [34][35][36][37][38][39]. Because of that, it was decided to increase the concentration of COD from 4000 to 10000 ppm, in order to give electrogenic microorganisms more opportunities to grow in this system.…”
Section: Electricity Productionsupporting
confidence: 56%
See 1 more Smart Citation
“…Because of the lack of organic substrate, it was difficult for the electrogenic microorganisms to compete efficiently, in particular taking into account the origin of the seeded sludge. This observation has been previously reported in the literature [34][35][36][37][38][39]. Because of that, it was decided to increase the concentration of COD from 4000 to 10000 ppm, in order to give electrogenic microorganisms more opportunities to grow in this system.…”
Section: Electricity Productionsupporting
confidence: 56%
“…In the particular case of two well-known electroactive microorganisms: Shewanella and Geobacter, it has been reported [37,39,41] that a maximum growth rate of 2.4 d -1 can occur, whereas other anaerobic non electrogenic microorganisms present higher maximum specific growth rate values [34,42]. The different growth rates would lead to mixed cultures, enriched in electrogenic microorganisms when operating at the high SRT.…”
Section: Electricity Productionmentioning
confidence: 99%
“…Analysis of Geobacter growth during bioremediation of uranium-contaminated groundwater revealed that growth rates estimated from gene transcript abundance were much higher than the actual increase in cell numbers in the groundwater (Holmes et al, 2013a). Furthermore, rates of subsurface Geobacter growth were significantly lower than the rates predicted by genome-scale metabolic models (Scheibe et al, 2009;Fang et al, 2011;Lovley et al, 2011;Zhuang et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Several parameters without traditional cultivation methods have been used to estimate microbial growth rate, e.g. microscopic cell density and cell size, adenosine 5 0 -triphosphate (ATP), assimilation rate of isotope labeled substrates (Karl et al 1980;Kirchman 2001;Malmstrom et al 2005;Torrton and Dufour 1996), microbial mat formation based on time-series observation (Taylor et al 1999), frequency of dividing cells (Newell and Christian 1981), macromolecular synthesis (Torrton and Dufour 1996), whole-genome microarray analysis (Holmes et al 2013). These methods were applied in the hydrothermal environments (Jannasch and Mottl 1985;Karl et al 1980) as well as general oceanic environments, and the calibration methods to convert growth rate or doubling time from these parameters have been developed (Kirchman 2001;Sherr et al 1999;Torrton and Dufour 1996;Yokokawa et al 2004).…”
Section: Introductionmentioning
confidence: 99%